Household Intimacy and Being Unmarried: Family Pluralism in the Novels of Anthony Trollope - Linda McClain; Allison Tait (Washington University Journal of Law and Policy, 2023)
Many critics rightfully claim that the marriage market and an inquiry into its innermost workings are at the heart of Anthony Trollope’s novels, but this Article argues that his novels also depict—on the periphery or sometimes just hiding in plain sight—a set of curiously nonmarital households. These households vary in form, but include widows and widowers living on their own, mothers and daughters living collectively, and male cousins sharing space and the work of daily living. Critics have debated whether Trollope was simply a realistic social historian— chronicling families as he found them— or whether he constructively used literary license to make broader points. On the first reading, Trollope presents a vast ecosystem of family pluralism, a terrain in which multiple kinds of families existed outside of the marital framework. Leaning more into literary imagination, it is possible to suggest that Trollope uses his range of household sketches to facilitate an exploration of how households and families can operate outside of the sexual and financial economies of marriage. In this context, his nonmarital households offer a rich composite portrait of how “functional” families operate, how the strength of intimacy flourishes outside of romantic relationships, and the challenges of maintaining a household outside of the marital norm. This Article offers a study of Trollope’s nonmarital families, with extended analysis of five novels in particular, The Bertrams, Rachel Ray, The Small House at Allington, Ralph the Heir, and Mr. Scarborough’s Family. In so doing, the Article presses on the question of Trollope's approach by exploring how he engages in both undertakings: to capture the range of domestic households both in small villages and the heart of Mayfair, and also to imaginatively explore the family as a site of affective possibility, multiple intimacies, and nonmarital ordering.
Keywords: Anthony Trollope; Marriage; Family; Pluralism; Household; Nonmarriage